DW Pengaruh Kepemimpinan Dan Disiplin Kerja Terhadap Kinerja Karyawan Koperasi Serba Usaha (KSU) Al –hudori Kecamatan Kertapati - Apriani, Dwi Wahyuni; Idris, M.; Puspasari, Mardiana (Yayasan Pendidikan Islam Amal Shaleh Kombongan, 2024)
This research aims to determine the influence of leadership and work discipline on the performance of employees of the Al-Hudori Multi-purpose Cooperative (KSU), Kertapati District. The sample used in this research was 63 respondents. The data used in this research are primary and secondary data. The data analysis used is qualitative and quantitative analysis. The analysis technique used is multiple linear regression. The results of multiple linear regression analysis show that Leadership and Work Discipline have a positive effect on employee performance. The results of simultaneous hypothesis testing show Fcount 32.112 > Ftable 2.39, meaning that there is a significant influence of Leadership and Work Discipline on employee performance. The partial hypothesis test results show a t-count value of Leadership 2.662, Work Discipline 5,288> 1.670, meaning that partially there is a significant influence of Leadership and Work Discipline on employee performance. The determination value shows that Leadership and Work Discipline are able to contribute to the ups and downs of employee performance, with the magnitude of the change caused by 50.1%.